Communicate...Reading and Writing Strategy (2023)
The research process was developed at the Antonio Baraya District educational institution located in Bogotá, south of the city, with first grade students. The general objective of the research was to implement a pedagogical strategy mediated by didactics and technology, which would strengthen the reading and writing processes of students, whose educational reality was disrupted by the covid-19 pandemic. The method used in this research was based on Action Research, the research paradigm was socio-critical, the research approach was qualitative of an ethnographic type; Regarding the research route, it was developed according to the stages, phases and transversal activities to the schedule, dates and the relationship with the proposed objectives. The elaboration of strategies (guides and digital tool) and their application were carried out taking into account the previous elaboration and implementation of the research instruments (questionnaire and interview) for data collection. In relation to the results, it was possible to show that the strategy implemented to strengthen the reading and writing process had a great impact on both the students and the first grade teachers, who report progress in said process according to the academic performance. In conclusion, the importance of generating pedagogical strategies that involve the use of technological tools that enhance and strengthen student learning from initial education, considering the context and current situation, as well as the support that the population requires to overcome the difficulties that arise.